Pengaruh Motivas Kerja, Pengalaman Magang dan Soft Skill terhadap Kesiapan Kerja Mahasiswa (Literatur Review Manajemen Pendidikan) - Barros da Cunha, Adilson; Erom, Kletus; Talok, Damianus (Jurnal Ilmu Manajemen Terapan, 2023)
This article is a literature review that reviews student work readiness which is influenced by work motivation, internship experience and soft skills. This study was conducted using previous and relevant research which is very useful for research and literature review in scientific work. The purpose of this article is to develop various hypotheses about the effect of variables that can be used in a study. The findings from this research are: 1) Work motivation is important and has a positive impact on student work readiness; 2) Internship experience is important and has a positive impact on student job readiness; 3) Soft skills are important and have a positive impact on student work readiness; 4) Work Motivation, internship experience and Soft Skills are important and have a positive impact on student work readiness.